2023
DOI: 10.3389/fenvs.2022.965841
|View full text |Cite
|
Sign up to set email alerts
|

The effects of energy taxes level on greenhouse gas emissions in the environmental policy measures framework

Abstract: Over the last decades, all countries have pursued an ambitious climate policy, thus showing a growing concern about climate change, global warming, greenhouse gas (GHG) emissions, or environmental taxes. Water, air, and soil pollution caused by gas emissions directly affect human health, but also the economies of states. As people’s ability to adapt to novel changes becomes increasingly difficult, globally, they are constantly trying to reduce their greenhouse gas emissions in a variety of ways. Environmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…Wang et al [17] analyzed panel data covering all Chinese provinces from 2000 to 2016, and they employed both a Dynamic Panel Data Model and a Panel Threshold Model to examine the influence of energy consumption structure and other factors on air pollution, and the results indicated that energy consumption structure contributes to air pollution in China's eastern, central, and western regions. Firtescu et al [18] empirically assessed, from 1995 to 2019, 28 countries in Europe and their effect of environmental tax levels on GHG emissions, and the results showed that in most countries, the increase in environmental taxes leads to a decrease in GHG emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [17] analyzed panel data covering all Chinese provinces from 2000 to 2016, and they employed both a Dynamic Panel Data Model and a Panel Threshold Model to examine the influence of energy consumption structure and other factors on air pollution, and the results indicated that energy consumption structure contributes to air pollution in China's eastern, central, and western regions. Firtescu et al [18] empirically assessed, from 1995 to 2019, 28 countries in Europe and their effect of environmental tax levels on GHG emissions, and the results showed that in most countries, the increase in environmental taxes leads to a decrease in GHG emissions.…”
Section: Introductionmentioning
confidence: 99%